Acute Kidney Injury Associated with Rapid Treatment of Hemodiafiltration for Bismuth Intoxication: Update and Review of the Literature (Annals of Medical Research, 2021)
None
Keywords: Acute Kidney Injury; Children; Colloidal Bismuth Subcitrate; Hemodiafiltration.